Mathematical wondrous in the Quran through Surah Al-Alaq - Ishak, Nur Dalila; Kilicman, Adem; Said Husain, Sharifah Kartini; Din, Rosseni (Universiti Kebangsaan Malaysia, 2020)
Personalized learning about the wondrous of the Creator as written in the Quran is important as it is limitless; and to search for it without themes and knowing what we are searching for would make one lost in his exploration. This paper demonstrates how numerical truths inherent between Surah Al-Alaq and the Quran based on Bediuzzaman Said Nursi ideas. Our prophet Muhammad (SAW) received the revelation of Surah Al Alaq as the first surah in the glorious Al-Quran. Thus, we study and showed the miracles that happens on how by only the first time surah Al-Alaq been revealed to Prophet Muhammad(SAW), it already portrays the geometric map as pattern of Al Quran even though manuscript of Al-Quran did not even exist yet at that time. This study hopefully can show the wondrous of the Al-Quran and provide materials to help those who want to personalize their learning about the wondrous of the Quran in regards to Mathematics gain awareness and evidence of the greatness of the Quran.